Anticandidal Activity and Mechanism of Action of Several Cationic Chimeric Antimicrobial Peptides - Memariani, Mojtaba; Memariani, Hamed; Moravvej, Hamideh; Goudarzi, Hossein; Robati, Reza Mahmoud (International journal of peptide research and therapeutics, 2023)
Antimicrobial peptides (AMPs) have recently been the subject of extensive research in both academia and commercial sectors because of their rapid, broad-spectrum microbicidal activity and a low likelihood of establishing drug resistance. Herein, we attempt to shed some light on anticandidal activity and mechanism of action of previously designed cationic chimeric AMPs, namely PV, BVP, PVP, and PV3. These four AMPs had a high tendency to adopt alpha-helical conformation based upon peptide structure prediction and circular dichroism. The geometric mean minimum inhibitory concentration (GMMIC) values (and ranges) of PV, BVP, PVP, and PV3 for all Candida albicans isolates (in µg/mL) were 1.83 (1–2), 93.33 (16 to >128), 3.25 (0.5–8), and 1.42 (0.5–2), respectively. At ≥ 8 µg/mL, all of the AMPs dose-dependently reduced in vitro viability of human fibroblast cells, with PV being the most cytotoxic peptide. Among the tested peptides, PV3 exhibited the highest cell selectivity index (determined as the ratio of CC 50 to GMMIC). Rapid candidacidal kinetics, disruption of cell wall/membrane integrity, and inhibition of yeast-to-hypha morphological switch were other important properties of the tested AMPs. Atomic force microscopy revealed that PV3 was able to induce major morpho-structural deformities in yeast cells such as blebs, cell shrinkage, and holes. Based on Fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectroscopy analysis, the polysaccharide content of the yeast cells was increased markedly in response to sub-lethal doses of PV3. Despite these encouraging data, much remains to be learned about in vivo efficacy and safety of these AMPs.